Ponderal Effect due to Changing Alkyl Substitution in a a Solvent and its Quantitative Correlation. - JESSY., J.M. (Asian Journal of Chemistry, 2010)
Effect of changing alkyl substitution in a solvent which has been reported as steric is demonstrated to be ponderal (mass) effect. The quantitative correlation between reactivity parameters and reduced molecular weights (of solute and solvent) in different reactions, indicated earlier as empirical, is shown to have theoretical basis as a relationship between solvation-dependent reactivity and ponderal substituent effect of alkyl groups (in solvent) on solvation.